Effect of zea mays hairs on hematological parameters - Sim, Chee Chew (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
The extract of Zea mays hairs was administered to Sprague Dawley albino rats with two dosages - 50mg/kg body weight and 1 OOmg/kg body weight. The rats were divided into four groups - control, 7 days treatment, 14 days treatment and 28 days treatment. After that the rats were sacrificed and the collected blood was tested for hematological analysis. The parameters used were RBC count, hemoglobin content, hematocrit level, total WBC count, WBC differential count and platelet count. Overall, the hematocrit level was significantly increased probably due to the diuretic effect of Zea mays hairs. WBC differential count also showed some degree of significance: neutrophil percentage was increased initially whereas both lymphocyte and eosinophil · percentage were reduced significantly.